A Critical Review of Orientalism, Post Modernism and Globalism - Shamsolmolok Mostafavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
« Orientalism, Post modernism, and Globalism are important topics each of which has led to the reflection and serious study of a number of contemporary thinkers on various fields of the humanities. Bryan Turner is one of the scholars who has explored these issues in a book with the same title and tried to clarify their relationship with one another. He argues in these series of subjects that not only globalization and post modernism have complicated the notion of "society" and thus challenged the legitimacy of thinking and the coherence of "sociology" itself, but they also affect all areas, including Orientalism. Emphasizing that the main threat to religious faith in a postmodern society is the commodification of everyday life, he urges intellectuals, in the light of the created shifts in the global nature of consumerism, to reflect on the traditional ways in which Orientalism has been discussed. The present article seeks to provide a critical analysis of his views by providing a content description of Turner's book.